Partial Stroke Testing of Emergency Shutdown Valve (Masoneilan) - MOHD HAFIZ BIN AHMAD SHAKIR, MOHD HAFIZ (Universiti Teknologi Petronas, 2009)
This documentation presents the basic research on Emergency Shutdown (ESD) valves testing design requirements to conduct the valves control. The inability to conduct Full Stroke Tests (FST) during the Partial Stroke Tests (PST) has forced this research to be conducted. Basically the project is about designing and programming a controller using software for controlling the f inal element instrument device in this case the emergency shutdown valve to open and close. The significant of this project is to overcome the inability of Emergency Shutdown System valve in the plant or platform to operate sm oothly and successfully. In current situation, most of the final element valve failed to conduct the Full Stroke Tests due to ESD valves become stuck since the ranging years for the testing is about 3 to 5 years. This project will also emphasize in designing the logic controller using Ladder Logic Diagram on a Programmable Logic Controller (PLC). There are two (2) methods being implemented to complete this project successfully which would involve designing and testing procedures. Both steps are implemented to get the data for analysis purpose in the final part of the project. In order to understand and perform well , some and further research have been done to understand the software and the instrument itself. Basic knowledge of Partial Stroke Testing and Full Stroke Testing has been mastered as well as the software for developing the system. From the early results and findings, the project has reached the basic objective that is to perform the Full Stroke Test during the Partial Stroke Test. For better analys is and results oriented, there should be some improvement to be done including the software configuration and parameters.